Effect of Anodes on Hydrodynamic Coefficients of Tubular Cylinders - Model Tests - Kurian, V.J. (2014)
This paper examines the hydrodynamic behavior of a tubular vertical cylinder with anode fittings subjected to regular waves. The model experiments were carried out in the wave basin of Universiti Teknologi PETRONAS. The model was made from galvanized steel, with outer diameter Do= 0.034 m and total length l = 1.23 m, fixed vertically to the soffit of the wave tank bridge, and the free end was immersed in the wave tank to form a cantilevered beam with wetted length of 0.85 m. Overall, seven anodes were welded to the wetted length of the tubular cylinder, at a center to center spacing of 0.12 m. The model was subjected to regular wave with Hmax varying from 0.1 m to 0.2 m, with wave height increment of 0.05 m, and the time period varying from T = 1 s to 3 s. The tests were conducted for Keulegan-Carpenter number ranging from 3.9 to 23.3. The hydrodynamic forces and the corresponding hydrodynamic coefficients of the smooth cylinder were compared with the force responses of a tubular cylinder with the same outer diameter, fitted with anodes. A scale factor of 1:55 was adopted in this experimental study based on the limitations of the maximum water depth in the wave tank, and the scaled up force responses of the full scale prototype were analyzed and discussed. The results show that, installation of anodes has increased the drag coefficients by up to 20% depending on the wave frequencies at which the model was tested.